Interleukin-6 and Mycobacterium tuberculosis dormancy antigens improve diagnosis of tuberculosis. Issue 2 (February 2021) - Adankwah, Ernest; Nausch, Norman; Minadzi, Difery; Abass, Mohammed K.; Franken, Kees L.M.C.; Ottenhoff, Tom H.M.; Mayatepek, Ertan; Phillips, Richard O.; Jacobsen, Marc
Highlights: IGRA-antigen long-term stimulation induced IFNg, IP-10, IL-22 and IL-6. IL-6 had the highest sensitivity for detection of M. tuberculosis infection. M. tuberculosis Rv1733/Rv2628 antigens induced cytokines were higher in contacts. Combined cytokine/antigen usage efficiently classified individuals from both groups. Abstract: Objectives: IFNγ-release assays (IGRAs) used for diagnosis of Mycobacterium (M.) tuberculosis infection have limited sensitivity. Alternative cytokines and M. tuberculosis latency-associated antigens may improve immune-based tests. Methods: Multiplex cytokine analyses was done in culture supernatants after 6-day in vitro restimulation with M. tuberculosis IGRA and latency-associated antigens (i.e. Rv2628, Rv1733) in tuberculosis patients ( n  = 22) and asymptomatic contacts (AC)s ( n  = 20) from Ghana. Results: Four cytokines (i.e. IFNγ, IP-10, IL-22 and IL-6) were significantly increased after IGRA-antigen specific restimulation. IFNγ, IP-10, and IL-22 correlated positively and showed no differences between the study groups whereas IGRA-antigen induced IL-6 was significantly higher in tuberculosis patients. Using adjusted IGRA criteria, IL-6 showed the highest sensitivity for detection of tuberculosis patients (91%) and ACs (85%) as compared to IFNγ, IP-10, and IL-22. Rv2628 and Rv1733 restimulation induced significantly higher IFNγ, IP-10, and IL-22 concentrations in ACs. Combined antigen/cytokine analyses identified study group specific patterns and a combination of Rv2628/Rv1733 induced IFNγ with IGRA-antigen induced IL-6 was optimal for classification of tuberculosis patients and ACs (AUC: 0.92, p <0.0001). Conclusions: We demonstrate the potency of alternative cytokines, especially IL-6, and latency-associated antigens Rv1733/Rv2628 to improve detection of M. tuberculosis infection and to classify tuberculosis patients and healthy contacts.